A selection of Ptolemaic anthropoid sarcophagi in Cairo - Leitz, Christian; Mahrous, Zeinab; Tawfik, Tarek (AUC Press archaeological reports., 2021)
"The individually designed anthropoid sarcophagi of the Ptolemaic period (ca. 330-30 BCE) offer a particularly rich and varied repertoire of hieroglyphic inscriptions and religious scenes. Being at the end of a long tradition of funerary literature, many of the epigraphs on these objects are variations or reinterpretations of older texts that have been circulated and transmitted over millennia. Others are entirely new creations that provide insight into funerary beliefs of late ancient Egypt. The present volume is the second and last publication of a joint project between scholars from Cairo University and the University of Tübingen on Late and Ptolemaic period sarcophagi housed in the museums of Cairo. It includes the detailed publication of eighteen sarcophagi, which until now have only been known through brief descriptions. The facsimile drawings, detailed pictures, translations and commentaries presented here will allow scholars to approach this corpus with a broad range of research questions."--